Science Inquiry-Based Activities in Elementary Education: How to Support Teachers' Practices? - Boaventura, D.M. (2020)
This investigation was done to understand how to support teachers to adopt innovative inquiry based science practices at elementary education. Here we present the results of two inquiry-based activities that were done in three elementary schools, involving six teachers and a total of 140 students. To understand the process of implementation of each activity by the teachers and its impacts on students, a qualitative methodology was used. The teachers were actively involved in the activities, however, the process followed by them was considerably different in what concerns time allocation. Additionally, instead of joining experiments from the different areas of conceptual knowledge, some of them chose only one separate subject. As a consequence, the students’ achievements were also different in each class. In the classes where the students had more time for discussion, more adequate answers were given to the initial questions, whereas, in the classes that devoted less time to the activity some competences, like observation skills and planning experiments were not achieved. It is suggested that although the creation of new curriculum materials can facilitate the adoption of new practices by teachers, this is not sufficient. Teacher's ownership of the activities is perhaps the keystone of this entire process.